2021
DOI: 10.1186/s12939-021-01468-5
|View full text |Cite
|
Sign up to set email alerts
|

Financial protection effects of private health insurance: experimental evidence from Chinese households with resident basic medical insurance

Abstract: Background After achieving universal basic medical insurance coverage, Chinese government put the development of private health insurance (PHI) on its agenda to further strengthen financial risk protection. This paper aims to assess the level of financial protection that PHI provides for its insured households on the basis of resident basic medical insurance (RBMI). Methods We employed balanced panel data collected between 2015 and 2017 from the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Furthermore, this article identified several key determinants of CHE incidence and most of them were similar with prior studies [14,43,44]. As we expected, higher annual per capita household income and better self-rated health status of the household head were both significantly associated with lower CHE incidence.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, this article identified several key determinants of CHE incidence and most of them were similar with prior studies [14,43,44]. As we expected, higher annual per capita household income and better self-rated health status of the household head were both significantly associated with lower CHE incidence.…”
Section: Discussionsupporting
confidence: 83%
“…However, many studies showed that the insured tends to utilize services that are exclusively covered by PHI, such as physical examinations, cancer screening, innovative drugs, and so on ( 38 , 39 ), to better manage their current health conditions. The results revealed that although the use of relatively expensive services such as hospitalization did not increase ( 40 ), the insured received more valuable health services and reduced financial risks ( 41 , 42 ). Contrastingly, the second path is more cost effective, consistent with the current popular and advanced concept of value-based insurance design (VBID) ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that of all individuals, the proportion of enrolled individuals shows an increasing trend year by year, with 8.7%,11.8% and 14.1% enrolled in CMI in 2015,2018 and 2021, respectively. This is also a significant increase compared to the 6.9% coverage rate estimated from the China’s National Health Service Survey in 2013 [ 33 ]. However, compared with the United States and some developed European countries, the coverage of CMI in China is relatively low.…”
Section: Discussionmentioning
confidence: 99%